The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1155/2023/2793211
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Thematics in a Brain‐Computer Interface Research

Abstract: This umbrella review is motivated to understand the shift in research themes on brain-computer interfacing (BCI) and it determined that a shift away from themes that focus on medical advancement and system development to applications that included education, marketing, gaming, safety, and security has occurred. The background of this review examined aspects of BCI categorisation, neuroimaging methods, brain control signal classification, applications, and ethics. The specific area of BCI software and hardware … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…The reason for this is that basic research on BCI has been accumulated over many years as a fundamental technology for Neurotechnology, and the term BCI has been included in the guidance by FDA-CDHR as well as in the consideration of industrial standards by the International Organization for Standardization (ISO) and the International Electrotechnical Commission (IEC). In this study, a bibliometric analysis of scholarly articles on BCI research in the Scopus data from 1982 to August 2022 ( Maiseli et al, 2023 ) and a survey study on bibliometric analysis of peer-reviewed review articles on BCI research extracted using One Search, a data mining tool that accesses 252 databases including BioOne, Google Scholar, JSTOR, ProQuest, and PubMed ( Alharbi, 2023 ) were referenced. The former is suitable for identifying general trends in BCI research for one of the world's largest scientific literature databases, while the latter is for peer-reviewed review articles extracted from a variety of scientific literature databases to identify trends in the countries including group of researchers with higher expertise and broader knowledge of BCI research.…”
Section: Procedures To Obtain Current State Of East Asia Through Quan...mentioning
confidence: 99%
See 4 more Smart Citations
“…The reason for this is that basic research on BCI has been accumulated over many years as a fundamental technology for Neurotechnology, and the term BCI has been included in the guidance by FDA-CDHR as well as in the consideration of industrial standards by the International Organization for Standardization (ISO) and the International Electrotechnical Commission (IEC). In this study, a bibliometric analysis of scholarly articles on BCI research in the Scopus data from 1982 to August 2022 ( Maiseli et al, 2023 ) and a survey study on bibliometric analysis of peer-reviewed review articles on BCI research extracted using One Search, a data mining tool that accesses 252 databases including BioOne, Google Scholar, JSTOR, ProQuest, and PubMed ( Alharbi, 2023 ) were referenced. The former is suitable for identifying general trends in BCI research for one of the world's largest scientific literature databases, while the latter is for peer-reviewed review articles extracted from a variety of scientific literature databases to identify trends in the countries including group of researchers with higher expertise and broader knowledge of BCI research.…”
Section: Procedures To Obtain Current State Of East Asia Through Quan...mentioning
confidence: 99%
“…While the number of academic papers published in China has been steadily increasing, Korea and Japan have shown a slowing trend in recent years, and Korea was to fall behind India in 2022. Table 2 summarizes the total number of academic papers based on Scopus data on BCI research ( Maiseli et al, 2023 ) and review articles extracted based on bibliographic data in One Search ( Alharbi, 2023 ), by country. While Japan has a relatively large number of academic papers published, it is surprising that the number of review papers published zero, as reported in Alharbi's paper ( 2023 ).…”
Section: Overview Of Objective Indicatorsmentioning
confidence: 99%
See 3 more Smart Citations